Eksistensi Perbankan Syariah Melalui Dominasi Pembiayaan Profit And Loss Sharing - Trimulato Trimulato (JPS (Jurnal Perbankan Syariah), 2021)
The beginning of the presence of the first Islamic bank in Indonesia was known as a bank with a profit and loss sharing concept. But in reality, profit and loss sharing financing is no longer dominant in Islamic banks, because non-profit sharing financing is more dominant, especially financing with the buying and selling model. The purpose of this research is to determine the development of financing in Islamic banks, as well as to determine the need to dominate profit-sharing financing in Islamic banks. This research is a qualitative descriptive which shows the development of Islamic bank financing products and the need to restore the concept of profit and loss sharing to be dominant in Islamic banks. The results of this study indicate that the growth of period financing is quite good. Then there are three reasons for the need to dominate profit and loss sharing financing in Islamic banks, namely restoring the identity of the Islamic bank as a profit-sharing bank, being the main differentiator between conventional and Islamic banks, and the opportunity to grow the real sector with greater income.